1987
DOI: 10.1080/00926238708403884
|View full text |Cite
|
Sign up to set email alerts
|

Sexual development and life of women with gonadal dysgenesis

Abstract: The sexual development and behavior of 37 women suffering from the gonadal dysgenesis syndrome were investigated. It was found that their sexual development was significantly retarded compared with a control group of 50 fertile patients of the same age. This retardation was greater in a subgroup of 19 women with the Turner syndrome than in a subgroup of 18 women with pure gonadal dysgenesis. The levels of gonadotrophins LH and FSH, estradiol, progesterone and testosterone in blood were similar in these two sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
5
1
9
Order By: Relevance
“…They have been reported to be less likely to be married or to be living in a steady relationship (Aran et al, 1992;Downey, Ehrhardt, Gruen, Bell, & Morishima, 1989;Holl et al, 1994;Nielsen, Nyborg, & Dahl, 1977;Tang, 1989), and those who do marry or engage in a stable relationship are reported to do so later than average (Aran et al, 1992;Nielsen et al, 1977;Pavlidis, McCauley, & Sybert, 1995). They are also reported to be less likely to be sexually active, and to have their sexual debut later (Downey et al, 1989;Nielsen et al, 1977;Pavlidis et al, 1995;Raboch, Kobilková, Horejší, Stárka, & Raboch, 1987).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…They have been reported to be less likely to be married or to be living in a steady relationship (Aran et al, 1992;Downey, Ehrhardt, Gruen, Bell, & Morishima, 1989;Holl et al, 1994;Nielsen, Nyborg, & Dahl, 1977;Tang, 1989), and those who do marry or engage in a stable relationship are reported to do so later than average (Aran et al, 1992;Nielsen et al, 1977;Pavlidis, McCauley, & Sybert, 1995). They are also reported to be less likely to be sexually active, and to have their sexual debut later (Downey et al, 1989;Nielsen et al, 1977;Pavlidis et al, 1995;Raboch, Kobilková, Horejší, Stárka, & Raboch, 1987).…”
mentioning
confidence: 81%
“…However, they reported wanting sexual activity one to two times a week, only slightly less than unaffected women. Raboch et al (1987) found that a heterogeneous group of women with gonadal dysgenesis, of whom half were diagnosed with TS, had an impaired sex life, characterized by a lower self-evaluated sexual desire and arousability, reduced orgasm capacity, and a lower level of sexual activity, compared with a group of healthy women of the same age. An interesting finding was that sexual functioning in the subgroup of women who had a stable partner relationship did not differ significantly from that of the comparison group of healthy women (Raboch et al, 1987).…”
mentioning
confidence: 98%
“…E FUNÇÃO SEXUAL Dificuldades de relacionamento amoroso são freqüen-temente relatadas por mulheres com ST (37); em comparação com a população como um todo, relatam ter suas primeiras experiências sexuais com mais idade, são sexualmente menos ativas e casam-se menos (23,30,33,38,44,46,48,49).…”
Section: Relacionamentos Amorososunclassified
“…Em comparação com a população como um todo, mulheres com ST relatam ter suas primeiras experiências sexuais com mais idade, são sexualmente menos ativas e casam-se menos 6,18,19,[22][23][24][25][26][27] .…”
Section: J Pediatr (Rio Junclassified